Are Banking Financial Performances and Green Banking Disclosure Associated with Bank Profitability? - Walzer, Michael; Tamimi, Abdul Hakim At; Firmansyah, Amrie (Accounting Student Research Journal, 2024)
This study examines how banking financial performance and green banking disclosure influence profitability. Financial performance in this research consists of capital adequacy ratio, non-performing loans, efficiency ratio, and loan-to-savings ratio. The research sample consisted of 30 samples selected using a purposive sampling method from 6 banking sector companies listed on the Indonesia Stock Exchange in 2018-2022, which consistently reported their green banking practices and did not experience losses during the research period. The analytical method in this research is panel data regression analysis. The research results show that the capital adequacy ratio and efficiency ratio have a negative effect on profitability. On the other hand, non-performing loans and the loan-to-deposit ratio positively affect company profits. Furthermore, green banking disclosure has a negative and significant effect on profitability. Implementing Green Banking can cause a decrease in profitability due to additional costs associated with its implementation. This research provides additional literature related to the implementation of green banking in Indonesia.